Synthesis of biowaste-derived carbon-dot-mediated silver nanoparticles and the evaluation of electrochemical properties for supercapacitor electrodes - Tenkayala, Navya Kumari; Maity, Chandan Kumar; Moniruzzaman, Md; Devaraju, Subramani (Beilstein Journal of Nanotechnology, 2025)
Herein, biowaste- (from Pongammia pinnata leaves) derived carbon dots (CDs) have been utilized as a mediator for the production of silver nanoparticles (PG-CDs-AgNPs) as a superior supercapacitor electrode. The methodology presented here is inexpensive and environmentally friendly as CDs play a role as capping, reducing, and stabilizing agent without addition of any chemicals. PG-CDs-AgNPs showed a particle size of 10 nm having excellent fluorescence emission in the blue region, and it has been explored as an electrode material for supercapacitor applications. The as-synthesized PG-CDs-AgNPs electrode exhibited the maximum specific capacitance of 540 F/g in a three-electrode study. The asymmetric supercapacitor (ASC) device with PG-CDs-AgNPs as the positive electrode reached the maximum specific capacitance of 200 F/g having a superior energy density of 71 W·h/kg at 1.5 A/g. Even at a high current density of 4 A/g, the ASC device reached a specific capacitance of 175 F/g, reinforcing its capability. The method described here provides a straightforward green approach towards biowaste-derived CD-mediated synthesis of AgNPs to produce efficient supercapacitor electrodes for energy storing.
Keywords: asymmetric supercapacitor; carbon dots; fluorescence emission; green approach; silver nanoparticles